Efektifitas Model Pendidikan Boarding School terhadap Peningkatan Karakter Kadet Mahasiswa Permesianan Kapal - Tnunay, Imanuel A. (Jurnal Ilmiah Mandala Education (JIME), 2022)
Boarding school is a system, where students, as well as teachers, and school managers live in dormitories that are in the school environment for a certain period of time. The education of shipping cadets uses the system. With the dormitory education model for shipping cadets is an effective educational model in educating intelligence, skills, character building and planting moral values in learners, or cadets so as to become more knowledgeable about the value of truth, honesty, virtue, wisdom, and compassion as universal values. All components of cognitive, affective and psychomotor education develop here. The problem is how character-based education patterns can form high-quality shipping cadets? Based on this study this time to find out the effectiveness of the boarding education model to improve the character of shipping cadets. With descriptive methods this research concludes that character education is very effective to form shipping cadets into reliable leaders in the future..  So as to be able to lead well in accordance with the principles of leadership has religious spiritual power and is able to uphold honesty, honor, responsibility, justice, caring, citizenship and having intelligence in work and decision making.